Imbalanced Liquidity Risk Management: Evidence from Latvian and Lithuanian Commercial Banks - Konovalova, Natalia; Zarembo, Julia (Copernican Journal of Finance & Accounting, 2015)
The nature of the liquidity risk lies in specific peculiarities of banking institutions activities. Thanks to a big amount of short-term resources banks can afford to offer long-term loans drawing their profit from higher interest rates on loans. It causes a situation with a discrepancy in the terms and the sums of assets and liabilities. As a result, the bank is exposed to the risk of being short of current liquidity in case a large number of depositors would like to withdraw their money. The bank is able to collect its resource base either by attracting additional deposits at higher interest rates or by means of a compelled unprofitable realization (selling) of its other assets. Apart from that, another source of potential liquidity problems is bank sensitivity to the fluctuations in interest rates: in case they grow, some of the depositors could withdraw their money in search of higher income in other deposits (investments); obtaining liquid assets by means of loan borrowing could prove to be more expensive while some kinds of loans could turn out to be unavailable. Taking into account the above-mentioned, the authors make a research of the problems of imbalanced liquidity in commercial banks considering the influence of both external and internal factors; reveal the reasons which have caused them, as well as expose the drawbacks in the imbalanced liquidity risk management.